한국의 아파트 실거래 매매 가격 분석을 통한 브랜드 가치 연구 - 이홍재; 이종우 (유통경영학회지, 2024)
Purpose: In Korea, apartments can be said to be the most common housing type. Existing p apers on h ome purchasing c onsumers m ainly f ocus o n the location o f the home, the quality o f the a rea, and home price evaluation. In particular, there are many papers on the importance of reputation, self-esteem, and emotional attachment in qualitative research. Af ter controlling for all other factors, the price difference resulting from the effect of the brand alone was effectively identified and analyzed to prove the effect of pure brand value alone. Research design, data, and methodology: In this paper, data f rom the Ministry of Land, Infrastructure and Transport of a total of 786,150 apartment sales in Seoul from 2013 to 2022 were used. The original data released by the Ministry of Land, Infrastructure and Transport includes the sale price of the apartment, apartment name and address, transaction date, apartment area (square meters), number of floors, and year of construction. Results: Among t he p hysical characteristic v ariables o f apartments, the eff ect of area was checked first, and it was f ound to have a positive (+) effect in all years. It is presumed that the increasing interest in apartment views when choosing an apartment has influenced the price. As for location factors, specific results were not obtained as the analysis results showed that apartment complexes could not be identified due to mountainous areas and rivers. Implications: Consumers’ valuation will ultimately result in differences in apartment prices by brand. Unlike previous studies, this study used the actual transaction prices of apartments in Seoul announced by the Ministry of Land, Infrastructure and Transport over the past 10 years to analyze the brand premium in monetary units and track changes over time. It was confirmed that the price contribution of apartment brands increased over time, and that ranking competition between brands was actively taking place.
Keywords: Brand Value; Real Estate marketing; Apartment Sales Prices